Progress in cryptology - AFRICACRYPT 2014 : 7th International Conference on Cryptology in Africa, Marrakesh, Morocco, May 28-30, 2014. Proceedings - Vergnaud, Damien; Pointcheval, David (Lecture Notes in Computer Science, 2014)
This book constitutes the refereed proceedings of the 7th International Conference on the Theory and Application of Cryptographic Techniques in Africa, AFRICACRYPT 2014, held in Marrakesh, Morocco in May 2014. The 26 papers presented  together with 1 invited talk were carefully reviewed and selected from 83 submissions. The aim of Africacrypt 2014 is to provide an international forum for practitioners and researchers from industry, academia and government from all over the world for a wide ranging discussion of all forms of cryptography and its applications as follows: Public-Key Cryptography, Hash Functions, Secret-Key Cryptanalysis, Number Theory, Hardware Implementation, Protocols, and Lattice-based Cryptography.